Communication as a strategic monetary policy tool : an evaluation of the effectiveness of the South African Reserve Bank's communication - Reid, Monique Brigitte (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.